Aclacinomycin enhances the killing effect of allogeneic NK cells on acute myeloid leukemia cells by inducing immunogenic cell death - Ye, Yongbin; Liu, Ning; Zeng, Yunxin; Guo, Ziwen; Wang, Xiaobo; Xu, Xiaojun (Frontiers in Immunology, 2025)
IntroductionNatural killer (NK) cells, which exert spontaneous cytotoxicity against infectious diseases and cancer, also play an important role in leukemia therapy. Despite the success of NK-based therapy in the treatment of myeloid leukemia, the potential use of NK alloreactivity in these hematologic malignancies remains elusive. The aim of the present study was to investigate whether allogeneic NK cells combined with aclacinomycin (ACM) could enhance anti-leukemic functionality against an acute myeloid leukemia (AML) cell line and to clarify the underlying mechanism. MethodsKG-1α and HL-60 AML cell lines were subjected to different treatments. The effects of different drug combinations on cytotoxicity, cell viability, and apoptotic status were examined. ResultsThe results showed that the combination of ACM (40 nmol/l) and allogeneic NK cells (ratio 20:1) was significantly cytotoxic to AML cells and increased the apoptosis of AML cells, especially after 72 h of treatment. Subsequent analyses revealed that the expression of immunogenic cell death (ICD)-related molecules calreticulin, adenosine triphosphate, and high mobility group box 1, as well as NK cell effector production—perforin and granzyme B—was markedly increased in the combination treatment group. These findings suggest that ACM enhances the anti-leukemic activity of allogeneic NK cells through the ICD pathway. DiscussionThese results demonstrated that allogeneic NK cells had enhanced functional responses when stimulated with ACM in vitro, exhibiting superior effector cytokine production and cytotoxicity compared to the control, which contained conventional NK cells. In conclusion, the present study suggested that the combination of ACM and allogeneic NK cells is a promising therapeutic strategy against AML.